PENDEKATAN LIVING VALUES EDUCATION DALAM PEMBELAJARAN PAI DAN BUDI PEKERTI SEBAGAI UPAYA MEMBENTUK ISLAMIC VALUE MORALITY PESERTA DIDIK - Rofi’ah Nurhayati (EL-TARBAWI, 2018)
Islamic religious education and Manners is one of the principal subjects in every level of education in Indonesia. Through these subjects, expected learners have appropriate moral with the teachings of the Islamic religion (Isamic Values Morality). In fact, the Islamic religious education and learning Manners hasn’t been fullest fruition, as evidenced by the diverse social irregularities committed by learners good level of elementary or high school. Therefore it is important to let the learning approach using a model Living Values Education (LVE). Because it is a personal approach with LVE mengidupkan twelve values (peace, respect, love, responsibility, joy, cooperation, honesty, humility, tolerance, simplicity and unity) that can assist in safely Isamic Values Morality. LVE then approaches through learning can be felt with the heart as well as implemented in everyday life by not forgetting that the educator is a great model for learners. The existence of the consistency between words and deeds of educators is crucial. The application of the approach to learning PAI and LVE in manners can be performed on the stage of the opening, the core and close by bringing positive energy like smiling and always appreciate as well as providing convenience for learners. so educators will get his heart and make it easy for yourself to develop the Isamic Values Morality as well as applied in everyday life. Keywords: Living Values Education (LVE), Islamic Education Learning and Manners, Islamic Values Morality